Chagas Immunochromatographic Rapid Test in the Serological Diagnosis of Trypanosoma cruzi Infection in Wild and Domestic Canids - Rodrigues, Esthefany S.; Santos, Gilbert Q.; Silva, Marlon Vicente da; Barros, Juliana H. S.; Bernardo, Aline R.; Diniz, Rafaela L.; Rubim, Nara M.; Roque, André L. R.; Jansen, Ana Maria; Silva, Edimilson D.; Xavier, Samanta C. C. (Frontiers in Cellular and Infection Microbiology, 2022)
Canis lupus familiaris (domestic dog) represents a reliable sentinel for the occurrence of a well-established transmission cycle of Trypanosoma cruzi among wild mammals in the surroundings and, consequently, where the risk of human infection exists. Serological diagnosis is the chosen method to identify T. cruzi infection in dogs that, in Brazil, rarely present positive parasitological tests. The use of recombinant chimeric parasitic antigens results in a sensitive and specific serological diagnostic test in contrast to the use of crude T. cruzi antigens. Our objective was to evaluate the Chagas/Bio-Manguinhos Lateral Flow Immunochromatographic Rapid Test (Chagas-LFRT) for the diagnosis of T. cruzi infection in domestic dogs and the potential of application of this diagnostic platform to wild canid species. Two recombinant proteins (IBMP-8.1 and IBMP-8.4) that displayed the best performance in the enzyme immunoassay (ELISA) in previous studies were tested in a platform with two diagnostic bands. A panel of 281 dog serum samples was evaluated: 133 positive for T. cruzi by serological diagnosis, including 20 samples with positive blood cultures belonging to different discrete typing units (DTUs); 129 negative samples; and 19 samples from dogs infected by other trypanosomatids: Leishmania infantum, Trypanosoma rangeli, Trypanosoma caninum and Crithidia mellificae, in addition to samples infected by Anaplasma platys, Dirofilaria immitis and Erlichia sp. that were employed to evaluate eventual cross-reactions. We also evaluated the Chagas-LFRT to detect T. cruzi infection in 9 serum samples from six wild canid species. We observed that the intensity pattern of the bands was directly proportional to the serological titer observed in IFAT. The sensitivity was 94%, the specificity was 91% according to the ROC curve, and the defined cutoff was an optical density of 4.8. The agreement obtained was considered substantial by the kappa analysis (84%). From T. cruzi positive hemoculture samples, 88.9% were positive by Chagas-LFRT. The test was efficient in recognizing infections by five of the six T. cruzi DTUs. Cross-reactions were not observed in infections by L. infantum, T. rangeli, T. caninum and D. immitis; however, they were observed in sera of dogs infected by Crithidia mellificae, Anaplasma sp. and Erlichia sp. A strong reaction was observed when serum samples from wild canids were submitted to the Protein A affinity test, confirming its applicability for these species. This test will allow rapid preventive actions in areas with high risk to the emergence of Chagas disease in a safer, reliable, low-cost and immediate manner, without the need for more complex laboratory tests.